Konvergensi Hukum Islam dan Undang-Undang Perlindungan Anak dalam Perkawinan Anak di Indramayu - Fikri, Arif; Burhanuddin, Ahmad; Santoso, Rudi; Ismail, Habib (Tasyri' : Journal of Islamic Law, 2025)
The practice of child marriage in Indramayu Regency remains a complex social issue, despite various efforts being made to address it. This study aims to analyze the convergence between Islamic Law and the Child Protection Law in handling child marriage cases in the region, as well as to identify the factors that influence the success or failure of the implementation of both legal systems in protecting children's rights. The method used is qualitative research with a case study approach, where data is obtained through in-depth interviews with relevant informants, field observations, and document and secondary data analysis. The research findings show that although Islamic Law allows child marriage under certain conditions, the Child Protection Law explicitly prohibits it to safeguard children's rights. However, the implementation of both legal systems is often hindered by social, cultural, and economic factors, such as poverty, arranged marriages, and the mental and physical unpreparedness of children for marriage. The synergy between the two in the local context has not been fully optimized, although there have been efforts to strengthen policies from the local government, including the enhancement of education and supervision. Therefore, this study recommends the need to strengthen policies, raise public awareness, and foster synergy between the government, legal institutions, and civil society organizations to prevent child marriage practices and protect children's rights in Indramayu Regency.